Therapeutic potential of traditional Chinese medicine for the treatment of NAFLD: A promising drug Potentilla discolor Bunge - Longshan Ji; Qian Li; Yong He; Xin Zhang; Zhenhua Zhou; Yating Gao; Miao Fang; Zhuo Yu; Robim M. Rodrigues; Yueqiu Gao; Man Li (Elsevier, 2022)
Nonalcoholic fatty liver disease (NAFLD) is characterized by excessive accumulation of hepatic lipids and metabolic stress-induced liver injury. There are currently no approved effective pharmacological treatments for NAFLD. Traditional Chinese medicine (TCM) has been used for centuries to treat patients with chronic liver diseases without clear disease types and mechanisms. More recently, TCM has been shown to have unique advantages in the treatment of NAFLD. We performed a systematic review of the medical literature published over the last two decades and found that many TCM formulas have been reported to be beneficial for the treatment of metabolic dysfunctions, including Potentilla discolor Bunge (PDB). PDB has a variety of active compounds, including flavonoids, terpenoids, organic acids, steroids and tannins. Many compounds have been shown to exhibit a series of beneficial effects for the treatment of NAFLD, including anti-oxidative and anti-inflammatory functions, improvement of lipid metabolism and reversal of insulin resistance. In this review, we summarize potential therapeutic effects of TCM formulas for the treatment of NAFLD, focusing on the medicinal properties of natural active compounds from PDB and their underlying mechanisms. We point out that PDB can be classified as a novel candidate for the treatment and prevention of NAFLD.